2014
DOI: 10.1016/j.jams.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Fluidity Caused by Electroacupuncture Stimulation

Abstract: In Oriental medicine, the state of blood stagnation is called "Oketsu," meaning preceding state or symptomatic of sickness. Acupuncture stimulation is often used clinically for the treatment of "Oketsu." The degree of "Oketsu" is indicated by tongue color and form, swelling, paroxysmal blushing, and dark circles under the eyes. The blood's fluidity is generally thought to be a blood stagnation factor. "Oketsu" is now considered as physiological blood flow and is studied from the perspective of the blood's flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The SB state can be evaluated by the criteria presented by Terasawa et al [5], and the diagnostic criteria are popularly called the SB score (Table 1). Recent studies have demonstrated that SB is correlated with a deterioration of erythrocyte deformability [6], an elevation in blood viscosity [7], acceleration of erythrocyte aggregation [8], blood fluidity [9][10][11], autonomic nervous activity changes [12], and microcirculatory dysfunction [13]. In this way, the pathological conditions of SB have been clarified scientifically.…”
Section: Introductionmentioning
confidence: 99%
“…The SB state can be evaluated by the criteria presented by Terasawa et al [5], and the diagnostic criteria are popularly called the SB score (Table 1). Recent studies have demonstrated that SB is correlated with a deterioration of erythrocyte deformability [6], an elevation in blood viscosity [7], acceleration of erythrocyte aggregation [8], blood fluidity [9][10][11], autonomic nervous activity changes [12], and microcirculatory dysfunction [13]. In this way, the pathological conditions of SB have been clarified scientifically.…”
Section: Introductionmentioning
confidence: 99%
“…6 Decreasing blood fluidity can cause circulatory-system disorders-such as arterial sclerosis or embolization-and cause vascular endothelial-cell damage due to hypertension; degradation of glucose tolerance; chronic inflammation; degradation of blood-vessel flexibility due to hyperlipidemia and aging; weakness of blood cells; and plasma plasticity degradation. 7 Currently, blood viscosity is known as cardiovascular disease (CVD) indicators for peripheral arterial disease, arterial hypertension, diabetes mellitus, high cholesterol and triglyceride levels, and crescent anemia. 8 Anticoagulant or antithrombotic therapy is often used in patients with a risk of venous thromboembolism (VTE) who are either hospitalized or who will undergo an examination or therapy procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the disturbances are also caused by various factors such as increased blood viscosity, active oxygen species, decreased erythrocyte deformability, coagulation/fibrinolysis system, and adhesion factors. In Kampo medicine (traditional Japanese medicine), these complex microcirculatory disturbances are referred to as oketsu (impaired microcirculation) [ 1 , 2 ]. Keishibukuryogan (KBG), tokishakuyakusan (TSS), and kamisyoyosan (KSS) have been used as oketsu-improving drugs (antioketsu drugs), with KBG particularly showing potent improving effects [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%